The van der Waals heterostructures of blue phosphorene with GaN/GeC for high-performance thermoelectric applications - Iqtidar Ahmad; Xue-Peng Wang; Ismail Shahid; Anwar Ali; Syed Hatim Shah; En Li; Tu Lyu; Keyuan Ding; Xin Chen; Feng Rao (APL Materials)
Thermoelectric devices have substantial potential as an environmentally compatible and sustainable power source to produce electricity straight out of waste heat. In this article, the density functional theory and Boltzmann’s transport equation are employed to investigate the thermoelectric characteristics of blue phosphorene (P)/GaN and P/GeC van der Waals heterostructures (vdWHs). Both vdWHs exhibit a small lattice thermal conductivity at 300 K because of the enhanced phonon boundary dispersion. P/GaN and P/GeC vdWHs drive an impressive boost in the figure of merit (ZT), achieving remarkable values of 5.07 and 4.67 at their respective effective temperatures. Moreover, both vdWHs possess an average ZT as high as 3.91 (P/GaN) and 3.44 (P/GeC). We also observed that these vdWHs exhibit an excellent conversion efficiency, up to 26% (P/GaN) and 25% (P/GeC) at 700 K. Our findings demonstrate that both vdWHs have practical potential for thermoelectric applications, representing significant progress in developing better thermoelectric devices.